PLP-independent racemization: mechanistic and mutational studies of O-ureidoserine racemase (DcsC). Issue 7 (24th January 2018) - Ahn, Yeong-Chan; Fischer, Conrad; van Belkum, Marco J.; Vederas, John C.
Abstract : Site-specific mutagenesis and inhibition of O -ureidoserine racemase reveals mechanistic insights in the unique PLP-independent bioenzymatic racemization of amino acids. Abstract : O -Ureidoserine racemase (DcsC) is a PLP-independent enzyme in the biosynthetic route to the antibioticd -cycloserine. Here we present the recombinant expression and characterization of a significantly more active DcsC variant featuring an N-terminal SUMO-tag. Synthesis of enantiomeric pure inhibitors in combination with site-specific mutation of active site cysteines to serines of this enzyme offers closer insights into the mechanism of this transformation. Homology modelling with a close relative (diaminopimelate epimerase, DapF) inspired C- and N-terminal truncation of DcsC to produce a more compact yet still active enzyme variant.